Study the Effect of Eruca Sativa Leaves Extract on Male Fertility in Albino Mice - Hussein, Zena F (Al-Nahrain Journal of Science, 2013)
This study was designed to determine the effect of Eruca sativa leaves extract on testosterone levels, sperm activity, mortality and abnormalities, and histological changes of testes.The aqueous leaves extract of E. sativa was prepared and then chemical detection was done. Results revealed that alkaloids, glycosides, flavonoids, saponins, coumarines, resin, terpens and steroidswere present in E. sativa extract. The fertility effect was carried out by treating mice with two doses (30 and 40) mg/Kg of extract. Results showed a significant (p≤ 0.05) increase in testosterone level, sperm activity and a significant decrease in sperm mortality and abnormalities were recorded.Histological changes in testicular section exhibited a significant increase in the diameter of seminiferous tubules, spermatid and leyding cells. A significant decrease in the interstitial space was noticed.